Wood-reinforced composites by stereolithography with the stress whitening behavior - Zhang, Shuyang; Bhagia, Samarthya; Li, Mi; Meng, Xianzhi; Ragauskas, Arthur J. (Materials & design, 2021)
[Display omitted] •First study on wood-flour-included composite by stereolithography.•Enhanced mechanical properties of the printed composites.•Stress-whitening was first found after the uniaxial drawing. In this study, poplar wood flour at various concentrations (1–10 wt%) is incorporated into a methacrylate-based resin via solution blending to fabricate wood-reinforced composites using stereolithography apparatus (SLA) 3D printing. Differential scanning calorimetry (DSC) along with Fourier transform infrared spectroscopy (FTIR) analysis shows the presence of a small amount of residual monomer in the printed samples. For the printed composites, the glass transition temperature (Tg) from dynamic mechanical analysis (DMA) decreases as more wood flour is incorporated, which indicates an increase in free volume occupied by polymer chains. The tensile strength is improved up to 17.3% from 21.1 MPa (no wood flour) to 24.7 MPa (1.0 wt% wood flour). The highest Young’s modulus reaches 323.8 MPa (2.0 wt% wood flour), which is 1.9-fold of that of the sample without wood flour. Moreover, the composites show “stress whitening” with the addition of wood flour during the uniaxial drawing. Morphology analysis of the tested samples show that the formation of microcraze and microvoids likely causing the stress whitening. This is the first study that demonstrates wood flour can be utilized in SLA 3D printed wood plastic composites (WPC) which can reinforce the printed products with a modest loading amount.